2017
DOI: 10.1007/s40266-017-0492-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Osteoporosis: From Pathophysiology to Therapeutic Approach

Abstract: The high worldwide prevalence of osteoporosis means it is considered a serious public health concern, possibly leading to physical disability and an increased mortality rate. Although osteoporosis is known as a silent disease affecting aging populations, its primary symptom remains pain. Acute pain is reported by patients with osteoporosis-related fractures, but chronic pain, mainly back pain, is also a characteristic of severe osteoporosis. Pain is associated not only with fractures but also with bodily chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 68 publications
4
36
0
Order By: Relevance
“…Importantly, pain management requires a multidimensional strategies to improve quality of life in patients with osteoporosis. 44 Our study indicated that antioxidant intervention may be a feasible approach to treat chronic pain in patients with osteoporosis. However, further clinical studies are necessary to determine the therapeutic potential of antioxidants in osteoporotic pain.…”
Section: A B C D Ementioning
confidence: 70%
“…Importantly, pain management requires a multidimensional strategies to improve quality of life in patients with osteoporosis. 44 Our study indicated that antioxidant intervention may be a feasible approach to treat chronic pain in patients with osteoporosis. However, further clinical studies are necessary to determine the therapeutic potential of antioxidants in osteoporotic pain.…”
Section: A B C D Ementioning
confidence: 70%
“…Chronic diseases are largely represented among the general population, and their incidence is constantly increasing all over the world. It has been recognized that affective and emotional symptoms, such as depression and anxiety, respectively, could embody predictors of several chronic diseases (Conversano et al, 2015;Catalano et al, 2017Catalano et al, , 2018Martino et al, 2018aMartino et al, ,b, 2019bKelly et al, 2019;Marchi et al, 2019). Particularly, psychological factors may compromise patients' compliance and adherence, and this could increase mortality and mobility independently from many confounders (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to plan and monitor treatments, an increasing number of studies have tried to identify the individuals' features and experience related to the illness across a variety of longterm chronic conditions such as osteoporosis (14), diabetes (15), chronic pain (16), dementia (17), and FMS (18) using comprehensive relevant questionnaires or outcomes measures provided by the medico-clinical research (19).…”
Section: Introductionmentioning
confidence: 99%